2017
DOI: 10.3347/kjp.2017.55.3.267
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Apoptosis: Pathological Basis of Behavioral Dysfunctions Induced by Angiostrongylus cantonensis in Rodents Model

Abstract: Angiostrongylus cantonensis invades the central nervous system (CNS) of humans to induce eosinophilic meningitis and meningoencephalitis and leads to persistent headache, cognitive dysfunction, and ataxic gait. Infected mice (nonpermissive host), admittedly, suffer more serious pathological injuries than rats (permissive host). However, the pathological basis of these manifestations is incompletely elucidated. In this study, the behavioral test, histological and immunohistochemical techniques, and analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
1
10
0
1
Order By: Relevance
“…The tracks and microcavities caused by the migration of larvae in the brains of infected animals, as described in previous studies [ 21 ], cannot explain all the clinical neurological injuries in the hosts [ 20 ] or the distinct outcomes between permissive and non-permissive hosts after A. cantonensis infection since the same physical destruction of neural tissue caused by the migration of larvae can be seen within both of their brains [ 11 ]. Interestingly, our previous [ 22 ] and the current findings indicate the obvious apoptosis and necroptosis of parenchymal and hippocampal astrocytes, neurons and microglia of mice infected with A. cantonensis (Figs. 3 – 10 ), which might provide new insights into the pathogenesis of neuroangiostrongyliasis.…”
Section: Discussionsupporting
confidence: 70%
“…The tracks and microcavities caused by the migration of larvae in the brains of infected animals, as described in previous studies [ 21 ], cannot explain all the clinical neurological injuries in the hosts [ 20 ] or the distinct outcomes between permissive and non-permissive hosts after A. cantonensis infection since the same physical destruction of neural tissue caused by the migration of larvae can be seen within both of their brains [ 11 ]. Interestingly, our previous [ 22 ] and the current findings indicate the obvious apoptosis and necroptosis of parenchymal and hippocampal astrocytes, neurons and microglia of mice infected with A. cantonensis (Figs. 3 – 10 ), which might provide new insights into the pathogenesis of neuroangiostrongyliasis.…”
Section: Discussionsupporting
confidence: 70%
“…Clinical exploration and animal studies confirmed that A. cantonensis invading the central nervous system caused neurological manifestations with behavioral dysfunctions (Hidelaratchi et al, 2005; Luo et al, 2017; Mengying et al, 2017). In the current study, we clearly elucidated that A. cantonensis infected mice exhibited dysfunctions of movement and cognition in a water maze task.…”
Section: Discussionmentioning
confidence: 86%
“…Eosinophilic meningitis in mice induced by A. cantonensis is characterized by infiltration of eosinophil and inflammatory cells and neuronal apoptosis (Luo et al, 2017). HDACi has long been used to treat neurodegenerative diseases (Hahnen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenic mechanisms involved in CNS parasitic infections consist of direct damage caused by the proliferation of protozoan parasites (Schluter and Barragan, 2019) and the physical disruption of tissue by migrating worms (Finsterer and Auer, 2013), while indirect injuries include alterations in the immune status of the CNS (Parlog et al, 2015), the modification of the function and structure of infected cells and the induction of programed cell death of host cells (Zhang et al, 2014;Halonen, 2015;Eugenin et al, 2019). Our previous studies indicated that apoptosis and necroptosis clearly occur in the hippocampal and parenchymal neurons, astrocytes and microglia of infected mice (Luo et al, 2017;Zhang et al, 2017). To further reveal the pathogenesis in permissive hosts infected with A. cantonensis, RT-qPCR, western blot analysis and immunofluorescence (IF) were applied to determine apoptosis, necroptosis, autophagy, and pyroptosis levels in the hippocampus and parenchyma of the rats.…”
Section: Introductionmentioning
confidence: 99%